PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK UNTUK MENGEMBANGKAN KEPEDULIAN PESERTA DIDIK TERHADAP LINGKUNGAN - Oktavian, Catur Nurrochman (Indonesia University of Education, 2015)
The research was prompted by students’ lack of environmental awareness. Cultivating concern and responsibility for environmental awareness can be carried out through social studies teaching and learning. In general, the research aimed to see differences in the effectiveness of project-based learning model in social studies teaching and learning in the experimental class and the use of problem-based learning model in the control class to develop students’ environmental awareness. It employed quantitative approach with quasi-experimental method. The design used was Non-Equivalent Pretest-Posttest Control Group Design. The population of this research included all seventh graders of SMP Negeri 1 Kemang, Bogor Regency. Students’ environmental awareness appeared to improve after teaching and learning, as can be observed from their discipline in putting trash to its place, communal work to clean up scribbles on the desk and classroom walls, and active participation in keeping the classroom clean. The research results also show positive responses from students because project-based learning gives project assignments that provided them with opportunities to develop their confidence and hone their creativity. Students’ activity in teaching and learning increased, as observed from their active involvement and independence in completing the projects during the teaching and learning process. Teachers responded positively and viewed that social studies teaching and learning process implementing project-based model had more advantages, namely: It could improve teachers’ knowledge and understanding of the syntax of innovative learning models and improve their abilities and skills in managing, organizing, and conducting instruction in the classroom. The obstacles encountered in the implementation of this project-based learning model were time allocation and the long preparation for teachers in order for the model to work well.Keywords: project based learning model, environmental awareness, social studies.